2018
DOI: 10.1161/circheartfailure.117.004302
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Sacubitril/Valsartan for the Management of Patients With Heart Failure

Abstract: Adoption of sacubitril/valsartan after Food and Drug Administration approval has been slow and may be associated with the high cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 30 publications
8
56
0
4
Order By: Relevance
“…Similar to the results of prior studies that found low adoption of sacubitril/valsartan treatment in the United States, we found that only 34 patients with HFrEF at VAGLAHS had an active prescription as of November 1, 2017 . Despite our findings of underuse of sacubitril/valsartan in eligible patients, the proportions of patients taking an ACEi/ARB, β‐blocker, or mineralocorticoid antagonist medications suggest that patients at VAGLAHS are managed according to evidence‐based guidelines.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the results of prior studies that found low adoption of sacubitril/valsartan treatment in the United States, we found that only 34 patients with HFrEF at VAGLAHS had an active prescription as of November 1, 2017 . Despite our findings of underuse of sacubitril/valsartan in eligible patients, the proportions of patients taking an ACEi/ARB, β‐blocker, or mineralocorticoid antagonist medications suggest that patients at VAGLAHS are managed according to evidence‐based guidelines.…”
Section: Discussionsupporting
confidence: 84%
“…12 Similar to the results of prior studies that found low adoption of sacubitril/valsartan treatment in the United States, we found that only 34 patients with HFrEF at VAGLAHS had an active prescription as of November 1, 2017. [7][8][9] Despite our findings of underuse of sacubitril/ valsartan in eligible patients, the proportions of patients taking an ACEi/ARB, b-blocker, or mineralocorticoid antagonist medications suggest that patients at VAGLAHS are managed according to evidence-based guidelines. We found that 50.6% of patients were taking a mineralocorticoid antagonist, which is even higher than the 33% of patients prescribed this class of medications in the Change the Management of Patients with Heart Failure (CHAMP-HF) registry.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…[54] Despite this, there has been significant inertia with the uptake of sacubitril/valsartan into clinical practice; in the 18 months following FDA approval, <3% of patients in a USA cohort with HFrEF were prescribed sacubitril/valsartan. [55] Various reasons have been suggested to be contributing to this, including the belief that if patients are stable on an ACE inhibitor (or an ARB) then there is no reason to switch to an ARNI.…”
Section: Implementation Of Sacubitril/valsartan Into Clinical Practicementioning
confidence: 99%
“…The recruitment of the study started in November 2016 (which corresponds with the approval of sacubitril/valsartan in Spain), and ended in June 2018 prior to the publication of the PIONEER‐HF trial . The low rates of prescription of this drug may be explained by the generalized slow adoption, which has been extensively reported, and to the fact that recruitment was done during an admission for acute HF. Although diuretics are not considered a disease‐modifying therapy, higher doses in similar scenarios have proven to reduce the number of decompensations .…”
mentioning
confidence: 99%